Practical Approach To Red Hat Linux 9.0: Basic and Intermediate - Md Shah, Wahidah; Saaya, Zurina (Penerbit UTEM, 2007)
This book aimed primarily for students and users who are new to Red Hat Linux operating system. It provides the users with introduction to the DOS, SUN Solaris and Red Hat Linux operating system. The hands-on practice is to equip the users with a basic range of skills required for using the commands in manipulating systems especially in Red Hat Linux operating system platform.